Topological analysis reveals a PD-L1-associated microenvironmental niche for Reed-Sternberg cells in Hodgkin lymphoma - Carey, Christopher D.; Gusenleitner, Daniel; Lipschitz, Mikel; Roemer, Margaretha G.M.; Stack, Edward C.; Gjini, Evisa; Hu, Xihao; Redd, Robert; Freeman, Gordon J.; Neuberg, Donna; Hodi, F. Stephen; Liu, Xiaole Shirley; et al. (Blood, 2017)
Signaling between programmed cell death protein 1 (PD-1) and the PD-1 ligands (PD-L1, PD-L2) is essential for malignant Hodgkin Reed-Sternberg (HRS) cells to evade antitumor immunity in classical Hodgkin lymphoma (cHL). Copy number alterations of 9p24.1/CD274(PD-L1)/PDCD1LG2(PD-L2) contribute to robust PD-L1 and PD-L2 expression by HRS cells. PD-L1 is also expressed by nonmalignant tumor-associated macrophages (TAMs), but the relationships among PD-L1+ HRS cells, PD-L1+ TAMs, and PD-1+ T cells remain undefined. We used multiplex immunofluorescence and digital image analysis to examine the topography of PD-L1+ and PD-1+ cells in the tumor microenvironment (TME) of cHL. We find that the majority of PD-L1 in the TME is expressed by the abundant PD-L1+ TAMs, which physically colocalize with PD-L1+ HRS cells in a microenvironmental niche. PD-L1+ TAMs are enriched for contacts with T cells, and PD-L1+ HRS cells are enriched for contacts with CD4+ T cells, a subset of which are PD-1+. Our data define a unique topology of cHL in which PD-L1+ TAMs surround HRS cells and implicate CD4+ T cells as a target of PD-1 blockade. •Regionally localized PD-L1+ macrophages form a specialized microenvironmental niche for Hodgkin Reed-Sternberg cells in cHL. [Display omitted]